Astronomy (South yarra Macmillan, 2012)
Heroes of Australian Science: Astronomy by Jane Fitzpatrick explores the groundbreaking contributions of Australian astronomers and scientists in the field of astronomy. The book highlights the achievements of individuals who have shaped the understanding of the universe through their research and discoveries. It delves into the stories of these "heroes," focusing on their scientific journeys, challenges, and the impact of their work both in Australia and globally. Fitzpatrick emphasizes key contributions such as the development of cutting-edge telescopes, advances in radio astronomy, and Australia's role in international space research. Through a combination of personal anecdotes and scientific explanations, the book celebrates the curiosity, perseverance, and innovation that have defined Australian astronomy. It aims to inspire readers, especially young scientists, by showcasing how local talent has helped unravel some of the greatest mysteries of space.